How are driving licensure status, delay in driving licensure, and driving exposure associated with alcohol and drug use, parental monitoring knowledge, peer alcohol and drug use, and health, education, and employment of emerging adults? - Gao, Xiang, author; Li, Kaigang, advisor; Vaca, Federico E., committee member; Sharp, Julia, committee member; DeYoung, Wendy, committee member (Colorado State University. Libraries, 2023)
Independence and mobility facilitated by driving privileges could have a major impact on alcohol and drug use, parental monitoring knowledge, peer alcohol and drug use, and health, education, and employment of emerging adults. Driving privileges may provide emerging adults with the ability to move more freely, and that mobility may affect their access to drugs and alcohol. It may also mean that emerging adults with driving privileges were more likely to be in environments where alcohol and drugs were available. Parents of emerging adults with driving privileges may be more involved in monitoring their child's driving activities, resulting in higher levels of parental monitoring knowledge. Emerging adults with driving privileges were more likely to report a higher level of peer alcohol and drug use because having access to a car allowed them to spend more time with their peers and engage in alcohol and drug use. On the other hand, driving privileges may have positive impacts on the health, education, and employment of emerging adults. Having the ability to travel to places of employment and educational institutions may open more opportunities and allow for greater access to resources. This could lead to improved academic and professional outcomes. Overall, driving privileges may have both positive and negative impacts on alcohol and drug use, parental monitoring knowledge, peer alcohol and drug use, and health, education, and employment of emerging adults. It was important to consider these trade-off impacts when considering how to best support emerging adults in their development. My dissertation explored how were driving licensure status, delay in driving licensure, and driving exposure associated with alcohol and drug use, parental monitoring knowledge, peer alcohol and drug use, and health, education, and employment of emerging adults. Data was collected from a nationally representative sample of U.S. emerging adults starting at grade 10th for a seven-year longitudinal assessment. Having driving licensure in high school, no delay in driving licensure, and higher driving exposure were associated with higher levels of alcohol and drug use, higher levels of parental monitoring knowledge, higher levels of peer alcohol and drug use, better health, higher levels of education attainment, and more working hours in emerging adulthood. My dissertation could inform policymakers and practitioners on the importance of driving privileges in promoting the well-being of emerging adults.
Keywords: behavioral health; public health; teen driving privileges; parental monitoring knowledge; applied health; substance use